Tindak Pidana Korupsi dalam Penyaluran Kredit Usaha Rakyat oleh Pegawai Bank: Studi Putusan Nomor 29/Pid.Sus-Tpk/2023/Pn. Gto - Gumilar Guruh Pratama; Safik Faozi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines corruption offenses in the disbursement of People’s Business Loans (KUR) based on Judgment No. 29/Pid.Sus-Tpk/2023/PN.GTO. The results of the study indicate that the criminal acts occurred as a result of the abuse of authority through procedural violations in the KUR disbursement process, which caused financial losses to the state. The judge’s legal reasoning was deemed consistent with the facts revealed during the trial, as all elements of the corruption offense were proven to have been met. Furthermore, the application of Article 3 in conjunction with Article 18 of the Law on the Eradication of Corruption Offenses, in conjunction with Article 55(1)(1) of the Criminal Code, against the defendant was also deemed appropriate. Banks need to strengthen their internal oversight systems, improve verification procedures in the credit granting process, and conduct periodic compliance audits to minimize the occurrence of irregularities in the future.